Pelatihan Budidaya Sayuran Hidroponik Menggunakan Wick System dan Nutrient Film Technique System sebagai Usaha Pemberdayaan Masyarakat - Alghifara, Roisu Rusydata; Kumala, Fitria Zana (Empowerment, 2022)
Kalisari Village, which is located in Banyumas Regency, is a well-known tofu industrial center area, and tofu has become the economic foundation of the Kalisari village community. The number of tofu producers also makes a lot of waste generated. With the PPKM in progress during this pandemic, tofu production and people's incomes have decreased. Therefore, the author organizes a service program in the form of hydroponic training as a solution to present new economic opportunities while reducing waste in Kalisari village. This training is expected to increase public interest in cultivating hydroponic plants. This training is expected to increase public interest in cultivating hydroponic plants. This training activity was carried out on Friday, August 13, 2021 at the hydroponic management @djiwatani. The methods used in this training are the wick system and the nutrient film technique system (NFT). The results of the training show that the people of Kalisari village are interested in cultivating hydroponic plants, besides that this hydroponic cultivation can later become a new source of income for the community and is proven to be environmentally friendly because it does not use pesticides and does not cause waste.Desa Kalisari yang terletak di Kabupaten Banyumas merupakan daerah sentra industri tahu yang sudah terkenal, dan tahu sudah menjadi tumpuan ekonomi masyarakat desa Kalisari. Banyaknya produsen tahu juga menjadikan banyak limbah yang di hasilkan. Dengan berlangsungnya PPKM dimasa pandemi ini menyebabkan produksi tahu dan pendapatan masyarakat menjadi menurun. Oleh sebab itu penulis menyelenggarakan program pengabdian berupa pelatihan hidroponik sebaga usaha pemberdayaan masyarakat serta solusi untuk menghadirkan peluang ekonomi baru sekaligus mengurangi limbah di desa Kalisari. Adanya pelatihan ini diharapkan dapat meningkatkan minat masyarakat untuk membudidayakan tanaman hidroponik. Kegiatan pelatihan ini dilaksanakan pada hari Jum’at tanggal 13 Agustus 2021 bertempat di pengelolaan hidroponik @djiwatani. Metode yang digunakan pada pelatihan ini adalah wick system dan nutrient film technique system (NFT). Hasil dari pelatihan menunjukan bahwa masyarakat desa Kalisari tertarik untuk membudidayakan tanaman hidroponik, selain itu pembudidayaan hidroponik ini nantinya dapat menjadi sumber pendapatan baru bagi masyarakat dan terbukti ramah lingkungan karena tidak menggunakan bahan pestisida serta tidak menimbulkan limbah.